DECONTAMINATION OF AFLATOXIN M1 IN MILK THROUGH INTEGRATION OF MICROBIAL CELLS WITH SORBITAN MONOSTEARATE, ACTIVATED CARBON AND BENTONITE - K. Muaz; M. Riaz1 (Journal of Animal and Plant Sciences, 2020)
Aflatoxin M1 (AFM1) is a highly toxic milk contaminant that poses a grave threat to human health. Among various strategies proposed for AFM1 decontamination, use of microbes have been considered to be one of the suitable techniques. However, the use of microbial cells alone had not proven to be efficient at higher AFM1 levels. Moreover, the complex between microbial cell and AFM1 had been suggested to be weaker and is dissociated soon after its exposure to washings. The objective of this study was to enhance the AFM1 binding efficiencies of bacterial cells (C) belonging to Lactobacillus paracasei and Bacillus coagulans in the presence of activated carbon (CAC), bentonite (CBENT) and sorbitan monostearate (CSP60). The reduction of AFM1 was found to be directly proportional to the concentration of microbial cells. Heat killed and acid treated L. paracasei successfully reduced AFM1 in milk spiked at 0.2 µg/L to 89% and 100% in CBENT, 84% and 90% in CAC, 59% and 47% in CSP60 and, 51.5% and 42% in C, respectively. Among treatments involving B. coagulans, acid treated CSP60 proved to be least effective showing 44.6% reduction, while CBENT for both acid and heat treated along with acid treated CAC proved to be most effective by removing 100% AFM1. CBENT and CAC (acid and heat killed) among both bacterial strains showed the formation of most stable complex with AFM1 showing no release of detectable AFM1 after couple of phosphate buffer saline (PBS) washings. Among other treatments, CSP60 of heat killed cells formed most stable complex for both L. paracasei and B. coagulans with 19% and 22% release of initially bound AFM1, respectively. The results showed that the combination of microbial cells with activated carbon and bentonite may be used as an efficient and effective strategy to mitigate the problem of AFM1 in milk.
Keywords: Aflatoxin M1; decontamination; lactic acid bacteria; activated carbon; bentonite